Exogenous application of Atonik (sodium nitrophenolate) under skip irrigation regimes modulated the physiology, growth and productivity of Zea mays L. Issue 12 (15th October 2023) - Batool, Zarina; Ishfaq, Muhammad; Akbar, Nadeem; Zulfiqar, Usman; Anjum, Shakeel Ahmad; Shafiq, Muhammad; Nazir, Shahid; Aziz, Abida
ABSTRACT: Foliar application of Atonik (sodium nitrophenolate) at crop critical growth stages is expected to improve crop physiology, morphology, and productivity. The present field study was conducted at the University of Agriculture, Faisalabad in autumn season of 2018 and 2019. Water deficit conditions were imposed by skip irrigation method. Plants were treated with foliar application of Atonik 10 (mg L −1 ) to evaluate the physiological, morphological, yield, and yield causative attributes of maize grown under deficit irrigation treatments. Randomized complete block design (RCBD) with split plots arrangement was used to layout the experiment having three replications. It was revealed that application of Atonik improved the crop's physiological attributes: relative leaf water contents (RLWC by 10%), chlorophyll contents (14%), and carotenoids content (15%) under water deficit conditions. Similarly, Atonik application augmented the leaf length at maturity, the number of green leaves at harvesting, and the number of grains row −1 of maize by 7%, 20% and 12%, respectively. Moreover, the application of Atonik amended the 100-grains weight, grain yield, and biological yield by 8%, 9% and 20%, respectively. In crux, application of Atonik is an excellent strategy to alleviate the detrimental influence of water deficit on physiological, morphological, and yield causative attributes of maize.